A systematic review on methodological variation in acute:chronic workload research in elite male football players - Wang, A.; Healy, J.; Hyett, N.; Berthelot, G.; Okholm Kryger, K. (Science and Medicine in Football, 2020)
Objectives: To investigate and evaluate the methodological variation in research on acute:chronic workload ratio (ACWR) and injury in elite male football players.